Improving Amazon-like Review Systems by Considering the Credibility and Time-Decay of Public Reviews - Wang, B.-C.; Zhu, W.-Y.; Chen, L.-J. (Informatica)
Improving Amazon-like Review Systems by Considering the Credibility and Time-Decay of Public Reviews